Juridical Studies in the Supervisory Function for Land and Building Rental by Foreign Nationals (WNA) - Dinda Alfira Syahrani; Endang Sutrisno (Syntax Corporation Indonesia, 2026)
The practice of leasing land and buildings by foreign citizens (Warga Negara Asing/WNA) in Indonesia continues to develop along with increasing investment and economic activities in strategic areas, one of which is Pantai Indah Kapuk (PIK), North Jakarta. This study aims to examine the practice of land and building leasing by foreign nationals, the forms of legal smuggling that occur, and the supervisory function in preventing such practices. The research method used is a normative juridical method with statutory and conceptual approaches. Data were obtained through library research and interviews with the management of the PIK area in North Jakarta. The analysis was conducted based on agrarian law, civil law, immigration law, and regional regulations related to the supervision of building use by foreign nationals. The results of the study indicate that leasing practices by foreign nationals are, in principle, permitted as long as they comply with applicable legal provisions. However, in practice, there are indications of misuse of lease agreements by foreign nationals who enter Indonesia using visit or tourist visas but subsequently lease buildings for long-term periods to conduct business activities, such as restaurants, clothing trade, and mobile phone accessories businesses. Such practices potentially contradict Articles 1320 and 1337 of the Indonesian Civil Code because they contain an unlawful cause and may be categorized as legal smuggling